Study The effect of Microwave Furnace Heat Energy Effects On Mechanical Properties And Estimated Fatigue Life of AA2024-T3 and AA7075-T6 - AL-Qaisy, Ahmed Adnan; Al-Shamikh, Abduljabbar J.; Alwan, Ali Hussein (Al-Nahrain Journal for Engineering Sciences, 2017)
The research aims to make a comparison between two highly used aluminum alloy though studding the effects left by the microwave furnace wavelengths by (middle dry and amid aqueous solutions) on the mechanical properties and estimated fatigue life of highly resistant widely use aluminum alloy AA 7075-T6 and AA 2024-T3. Since the microwave effect differ from other heating methods through its effects (Heat Transfer) r heating methods effects on the surface of the alloy, which might change some of its properties as well as resistance to fatigue, also to see how this effect changes from alloy to another through this study. The results show some great effects on both mechanical properties and estimated fatigue life for both alloys but with different levels. This new technique is differing from other traditional heat treating ones that is simple, cheap and fast accurate method than the other techniques.There is a common misconception about the use of minerals in microwave ovens and the concept is unscientific and based on false grounds and simplest proof of that is that most of these ovens are built from the inside metal fully, how dangerous this is consistent? This research aims to focus on and remove those problematic and misconceptions.